The Implementation of Physical Literacy in Physical Education Learning to Support Lifelong Active Lifestyle - Nita Peranita; I Ketut Semarayasa; I Wayan Muliarta (Journal of Physical Education Health and Sport, 2025)
This study aims to analyze the implementation of physical literacy-based approaches within Physical Education (PE) learning to support students’ lifelong active lifestyles. Physical literacy is conceptualized as an integrated foundation of physical competence, motivation, confidence, knowledge, and understanding that enables individuals to engage in meaningful physical activities throughout life. A qualitative literature study was employed by reviewing 40 peer-reviewed articles published in the last ten years from Scopus-indexed journals and national accredited journals. Data were analyzed through thematic synthesis comprising extraction, categorization, and interpretation of recurring patterns. The findings indicate that physical literacy contributes significantly to the development of fundamental movement skills, intrinsic motivation, and sustained participation in physical activity. Effective implementation in PE requires student-centered pedagogical models such as Teaching Games for Understanding (TGFU), movement education, active play, and learning environments that encourage autonomy and meaningful engagement. The study concludes that integrating physical literacy into PE curriculum promotes long-term health behaviors and builds a strong foundation for lifelong active lifestyles. This research highlights the urgency for teachers to adopt holistic, inclusive, and motivational teaching strategies that nurture students’ physical literacy from early schooling.